Aksi Nyata Upaya Pemberantasan Tuberkulosis di Puskesmas Karanganyar Kab. Pekalongan - Nugroho, Santoso Tri; Winarsih, Hesti; Kurniasari, Putri; Nikmah, Nurul; Rizki, Nayla Kharismatul; Mafazati, Dewi; Anggraini, Hani; Kusuma, Ikpal Hamdan; Setianingsih, Setianingsih (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2026)
Background:Tuberculosis remains a serious public health challenge in Indonesia, including in Pekalongan City, which sees an annual increase in cases. The still high number of TB cases and deaths each year indicates that the program being implemented is not yet fully effective, therefore requiring active community involvement, increased capacity of health workers, and closer cross-sector integration. Aims: This activity aims to provide comprehensive community nursing care through a promotive and preventive approach, with an emphasis on identifying risky behaviors, knowledge deficits, and non-adherence to TB treatment. Method: The methods used included community assessment, establishing a community nursing diagnosis, planning education-based interventions, implementing outreach and simulation activities, and evaluating outcomes. Results: The results of the activity indicated that most people have limited knowledge about TB prevention, and that risky behaviors and non-adherence to therapy persist. Interventions, including group outreach, interactive discussions, and education on the importance of medication adherence, demonstrated increased knowledge and healthier behavior changes. Conclution: The conclusion of this activity emphasized the importance of the active role of community nurses in reducing TB transmission rates through educational approaches, active surveillance, and cross-sector collaboration. Recommendations focused on strengthening ongoing education and the involvement of families and community health workers in early detection and monitoring of TB patient therapy.